Design and Fabrication of Mini Multipurpose Cultivator and Tiller - Sah, Arun; Hyder, MD Ali; Sohan, Mohiuddin; Goyal, Ravinder; Gill, Kanwar Jabar Singh (Journal of Advanced Research in Mechanical Engineering and Technology, 2022)
A mini-multi-purpose cultivator and tiller is a farming or gardening tool that breaks up soil and removes weeds in the lines where plants are growing or will be grown. The soil cultivator and tiller are one of the important mechanizations of farming. Tractors, soil tiller, mini cultivator and weedier are non-conventional so far as the displacement of labour is concerned. Mini cultivator especially considering the fact that the majority of farmers are having small land, and it is also useful for trilling and weeding without destroying crops like groundnuts, paddy, soya bin crops, cultivation of sugarcane in particular, and other crops in general for the smaller farmers, which increases the productivity of crops. Small farmer Can hardly afford expensive tractors. So, the tiller and weeder is one of useful machine. How to cite this article: Sah A, Hyder MDA, Sohan M et al. Design and Fabrication of Mini Multipurpose Cultivator and Tiller. J Adv Res Mech Engi Tech 2022; 9(1&2): 6-12.